ROOT-CANAL MORPHOLOGY OF MANDIBULAR INCISORS - (:unkn) unknown (ELSEVIER SCIENCE INC, 1992)
In this study, 100 mandibular central and lateral incisors were used to determine the number of root canals and their types, the ramifications of the root canal, the location of apical foramina, and the frequency of apical deltas. The teeth were immersed in India ink, decalcified, and cleared. The examination of root canal systems of the teeth was based on Vertucci's classification. Two more root canal types which are not defined in that classification have also been determined and grouped as new types.
Keywords: ENDODONTICS